Afterword—The Racialized Past is Racist Prologue: The Relevance and Resonance of Historical Novels in the Age of Trump. (18th March 2021) - Schlund-Vials, Cathy J
Abstract: Situated adjacent to the essentializing logics and combative rhetorics that have largely defined the Trump administration's "war" on history, specifically regarding initiatives such as the "White House Conference on American History" and the "1776 Commission, " this afterword considers the distinctive significance and ongoing consequence of ethnic American literary engagements with a frequently debated and still unreconciled US past. To illustrate both the relevance and resonance of such literary productions, the afterword accesses Jackson Bliss's short story "Secret Codes & Oppressive Histories" (which is featured in the special issue) and briefly considers William Shakespeare's The Tempest, the source text for the oft-utilized notion that the past functions as prologue. By way of conclusion, the afterword turns to cultural critic Lisa Lowe's evocative articulation of "reckoning" as a productive and liberatory means of "revisit[ing] times of historical contingency and possibility to consider alternatives that may have been unthought in those times."